Use of Intravenous Immunoglobulins in Intensive Therapy - E. A. Latysheva; T. V. Latysheva (Общая реаниматология)
The main cause of death in the intensive care units is infectious complications, including sepsis and septic shock. Immunoglobulins are the most potent mechanisms in anti-infective defense. Whether intravenous immunoglobulins should be used in urgent situations remains to be solved. The mechanisms of action of immunoglobulins are diverse and depend on dosage and time of use. The paper analyzes the data available in the Russian and foreign literature on the possible points of use of intravenous immunoglobulins in the treatment of acute conditions accompanied by sepsis. It also gives the authors’ data on the use of intravenous immunoglobulins to treat toxic epidermal necrolysis. Key words: intravenous immunoglob-ulins, sepsis, toxic epidermal necrolysis.